Five known tagging DLL3 SNPs are not associated with congenital scoliosis: A case–control association study in a Chinese Han population - Yang, Yong; Wang, Bing-Qiang; Wu, Zhi-Hong; Zhang, Hai-Yan; Qiu, Gui-Xing; Shen, Jian-Xiong; Zhang, Jian-Guo; Zhao, Yu; Wang, Yi-Peng; Fei, Qi (Medicine (Baltimore), 2016)
Genetic etiology hypothesis is widely accepted in the development of congenital scoliosis (CS). The delta-like 3 (DLL3) gene, a member of the Notch signaling pathway, was implicated to contribute to human CS. In this study, a case-control association study was conducted to determine the association of single nucleotide polymorphism (SNP) in the DLL3 gene with CS in a Chinese Han Population. Five known tagging SNPs of the DLL3 gene were genotyped among 270 Chinese Han subjects (128 nonsyndromic CS patients and 142 matched controls). CS patients were divided into 3 types: type I-failure of formation (29 cases), type II-failure of segmentation (50 cases), and type III-mixed defects (49 cases). The 5 SNPs were analyzed by the allelic and genotypic association analysis, genotype-phenotype association analysis, and haplotype analysis. Allele frequencies of 5 tagging SNPs (SNP1: rs1110627, SNP2: rs3212276, SNP3: rs2304223, SNP4: rs2304222, and SNP5: rs2304214) in CS cases and controls were comparable and there were no available inheritance models. The SNPs were not associated with clinical phenotypes. Moreover, the 5 makers in the DLL3 gene were found to be in strong linkage disequilibrium (LD). Both global haplotype and individual haplotype analyses showed that the haplotypes of SNP1/SNP2/SNP3/SNP4/SNP5 did not correlate with the disease (P >0.05). Together, these data suggest that genetic variants of the DLL3 gene are not associated with CS in the Chinese Han population.